Ensino e Aprendizagem de Matemática Através da Resolução de Problemas Como Prática Sociointeracionista - Junior, Luiz Carlos Leal [UNESP]; De La Rosa Onuchic, Lourdes [UNESP] (FapUNIFESP (SciELO), 2015)
This article presents a truly practical experience and the approach of Teaching and Learning Mathematics through Problem Solving, as a sociointeractionist practice from its theoretical and philosophical constitutions to their educational practice in a course of the Programa Nacional de Acesso ao Ensino Técnico e ao Emprego headed by Instituto Federal de São Paulo-Campus Sertaozinho. We present a field of social, historic, and cultural studies as proposed by Problem Solving, not only as a teaching-learning methodology but rather as a field of study that keeps alive the move action /reflection/ action and through concepts and problems in Vygotskys work. Lay hold of the self-regulatory and metacognition elements by thinking-out-loud in the construction of knowledge and creation of learning and some consequences of this practice in schools.
Teaching and learning mathematics through problem solving as sociointeractionist practice
Keywords: Problem Solving; PRONATEC; Sociointeractionist Practice; Teaching-Learning; Thinking-Out-Loud